Second Generation Abl Kinase Inhibitors and Novel Compounds to Eliminate the Bcr-Abl/T315I Clone - Kimura, Shinya (Recent Patents on Anti-Cancer Drug Discovery, 2006)
The first line therapy for chronic myeloid leukemia (CML) was dramatically altered within a few years of the introduction of Abl specific tyrosine kinase inhibitor, imatinib mesylate to the clinic. However, refractoriness and early relapse have frequently been reported, particularly in patients with advanced-stage disease. Point mutations within the Abl kinase domain that interfere with imatinib mesylate binding are most critical cause of imatinib resistance. To override resistance, several second generation ATP competitive Abl kinase inhibitors such as dasatinib, nilotinib and INNO-406 have been developed. Although, these novel inhibitors can inhibit the phosphorylation of most mutated Bcr-Abl except T315I, no ATP competitive Abl kinase inhibitors, which can inhibit the phosphorylation of Bcr-Abl/T315I, has been developed. Thus, Bcr-Abl/T315I is an important and challenging target for discovery of CML therapeutics. This review is focused on the three novel compounds reported in the recent patents (2004-2006) which claim the efficacy against Bcr- Abl/T315I.
Keywords: imatinib mesylate